The Use of Video as a Learning Media in Science Learning (A Systematic Review) - Auliya Naimah (STAI Hubbulwathan Duri, 2022)
Video is the one of the learning media that can facilitate the learning process. This study aims to systematically review and analyze the results of research on the use of video in learning based on 42 articles searched from six online databases of Sciencedirect, Tandfondline, Sage, Google Scholar, Springer, and Emerald between 2019 – 2021. The method used is systematic literature review (SLR). The articles analyzed cover various levels of education, disciplines and the use of video in learning. The results of the analysis found that the use of video in learning tended to focus on increasing the effectiveness of learning (59.52%), exploring the influence of video in learning (23.81%), media development (9.52%) and the rest on general use and instrument development. Most studies adopt survey methodology (questionnaires or interviews) (40.48%), however there are mostly studies involving quantitative data sources (42.86%). The use of video in science learning can improve students' understanding and learning achievement.